A particle‐continuum coupling method for amorphous polymers with multiple particle‐based domains. Issue 1 (24th March 2023) - Torres Huamani, David; Zhao, Wuyang; Pfaller, Sebastian
Abstract: This contribution presents a partitioned‐domain particle‐continuum coupling method for amorphous polymers with multiple particle‐based domains. The coupling method treats the particle‐based domains with molecular dynamics (MD) simulations and the continuum domain discretized by the Finite Element (FE) method. In the continuum domain, a viscoelastic‐viscoplastic (VE‐VP) constitutive model derived from MD simulation results of the polymer at molecular resolution is employed. The effects of the minimum distances between the domains, the distribution and the number of the MD domains as well as the strain rates are studied under uniaxial tension. This method is a precursor for multiscale simulations of polymer‐based nanocomposites (PNC).